Acute Inflammatory Response to Low-, Moderate-, and High-Load Resistance Exercise in Women With Breast Cancer–Related Lymphedema. (September 2016) - Cormie, Prue; Singh, Benjamin; Hayes, Sandi; Peake, Jonathan M.; Galvão, Daniel A.; Taaffe, Dennis R.; Spry, Nigel; Nosaka, Kazunori; Cornish, Bruce; Schmitz, Kathryn H.; Newton, Robert U.
Background . Resistance exercise is emerging as a potential adjunct therapy to aid in the management of breast cancer–related lymphedema (BCRL). However, the mechanisms underlying the relationships between the acute and long-term benefits of resistance exercise on BCRL are not well understood. Purpose . To examine the acute inflammatory response to upper-body resistance exercise in women with BCRL and to compare these effects between resistance exercises involving low, moderate, and high loads. The impact on lymphedema status and associated symptoms was also compared. Methods . A total of 21 women, 62 ± 10 years old, with BCRL participated in the study. Participants completed low-load (15-20 repetition maximum [RM]), moderate-load (10-12 RM), and high-load (6-8 RM) exercise sessions consisting of 3 sets of 6 upper-body resistance exercises. Sessions were completed in a randomized order separated by a 7- to 10-day wash-out period. Venous blood samples were obtained to assess markers of exercise-induced muscle damage and inflammation. Lymphedema status was assessed using bioimpedance spectroscopy and arm circumferences, and associated symptoms were assessed using Visual Analogue Scales for pain, heaviness, and tightness. Measurements were conducted before and 24 hours after the exercise sessions. Results . No significant changes in creatine kinase, C-reactive protein, interleukin-6, and tumor necrosis factor-α were observed following the 3 resistance exercise sessions. There were no significant changes in arm swelling or symptom severity scores across the 3 resistance exercise conditions. Conclusions . The magnitude of acute exercise-induced inflammation following upper-body resistance exercise in women with BCRL does not vary between resistance exercise loads.